On Algebraic Properties of k-Q-Anti Fuzzy Normed Rings - Munusamy, Premkumar; Jeyapackiam , J. Juliet; Salam , Abdul; Bai , H. Girija; Immanuel , Y.; Prasanna , A. (On Algebraic Properties of k-Q-Anti Fuzzy Normed Rings, 2023)
In this paper, the concept of \(k\) - \(Q\) - Anti fuzzy normed ring is introduced and some basic properties related to it are established. That our definition of normed rings on \(k\) - \(Q\) - Anti fuzzy sets leads to a algebraic structure which we call a \(k\) - \(Q\) - Anti Fuzzy Normed Rings. We also defined \(k\) - \(Q\) - Anti Fuzzy Normed Rings homomorphism, Anti Fuzzy Normed Subring, Fuzzy Normed Ideal, \(k\) - \(Q\) - Fuzzy Normed Prime Ideal and \(k\) - \(Q\) - Anti Fuzzy Normed Maximal Ideal of a Normed ring respectively. We show that the some algebraic properties of normed ring theory on a \(k\) - \(Q\) - fuzzy sets, prove theorem and given relevant examples.